The Economy of the Body - Ghiselin, Michael T. (American Economic Review, 1978)
The process of interrelating disciplines takes many forms. In some cases there is simply an analogizing or a borrowing of jargon-perhaps a mere transfer of metaphor, as when we speak of body politic. In other instances one discipline provides useful tools for the study of others; for example, physics has given economics and biology units of measurement for the study of energy. Sometimes there is an area of overlap between two fields and a hybrid discipline arises: biochemistry and biophysics are good examples. Finally we have cases in which two disciplines are really branches of a more general one. The obvious example is zoology and botany forming subdivisions of biology. In the present work I shall take the position that economics and biology do not merely share common interests; they have more than just a few lessons to learn from one another, or an interdisciplinary boundary at which common problems are dealt with. Rather, they constitute a single branch of knowledge. Just as biology deals with both plant and animal life, there should be recognized a branch of knowledge that deals with economic processes irrespective of whether they are man-made or not, concerning itself with such phenomena as competition that are common to all economies. Thus I propose that we recognize a body of knowledge called naturall economy (biology) coordinate with political economy (economics), together forming a branch of knowledge which we may call genleral